PENGARUH PENGATURAN KERJA YANG FLEXIBEL, KESEIMBANGAN KEHIDUPAN KERJA DAN KETERIKATAN KARYAWAN TERHADAP LOYALITAS KERJA KARYAWAN PADA PERUSAHAAN PROPERTI DI KOTA KENDARI - VERA VEBRIANTHY VERA; Bakhtiar Abbas; H. Mahmudin A. Sabilalo (Halu Oleo University, 2022)
This study aims to determine, analyze and prove that employee work loyalty at a property company in Kendari City is partially influenced by flexible work arrangements, work-life balance, employee engagement. The research design used quantitative research with a field survey approach, Data analysis used SEM based on Partial Least Square with the help of Smart PLS Software. 3. The results of the study show that: (1) Flexible work arrangements do not have a positive and significant effect on employee work loyalty meaning that every time there is an increase in indicators on flexible work arrangements it does not significantly affect employee work loyalty.(2) )Work-life balance has a positive and significant effect on employee work loyalty at a property company in Kendari City, meaning that every time there is a change an increase in indicators on work-life balance can affect employee work loyalty,. (3) Employee engagement does not have a positive and significant effect on employee loyalty, meaning that every time there is an increase in the indicators of employee engagement it does not significantly affect employee engagement. affect work loyalty.